A Quantitative Analysis of Task-Based Language Teaching (TBLT) on EFL Students' Speaking Skills - Sultan; Nurdin Noni; Abdullah (International Journal of Language, Education, and Literature, 2026)
This study examines the effectiveness of Task-Based Language Teaching (TBLT) in enhancing speaking skills among 29 EFL junior secondary students at SMPN 3 Polongbangkeng Utara, Indonesia. Involving 29 junior high school students, this research employs a pre-experimental one-group pretest-posttest design. The results revealed that TBLT significantly improved students' speaking proficiency. The mean score for the pre-test was 34.90 (SD = 10.844), while the post-test mean score increased to 68.83 (SD = 11.680). A paired-sample t-test confirmed a statistically significant difference between the pre-test and post-test scores (t = 21.95, p < .001), indicating a substantial enhancement in speaking skills following the implementation of TBLT. The calculated effect size of Cohen's d = 2.99 supports the conclusion that TBLT had a large and significant impact on the improvement of students' speaking abilities. This significant improvement suggests that TBLT provides an effective method for boosting speaking proficiency in language learners. Furthermore, the results underline the importance of using meaningful tasks that encourage active language use and communication in real-world contexts. The findings offer strong evidence that TBLT can be a highly effective approach to enhance speaking skills, especially in contexts where traditional teaching methods may fall short. Generally, the study reveals that TBLT can lead to significant improvements in students' speaking skills, offering valuable insights into its potential as an instructional strategy for language learning. Keywords: Task-Based Language Teaching, speaking skills, EFL, quantitative analysis